The Tendency of Quiet Quitting Workers in Terms of Engagement and Well-Being at Work - Pundani Eki Pratiwi; Sugiyarta Stanislaus; Pradipta Christy Pratiwi (Philanthropy: Journal of Psychology, 2023)
This study aims to look at the phenomenon of quite quiting that exists in workers after returning to work activities in the office. This phenomenon is viewed from the engagement and well being of workers in the workplace. Quite quiting itself is a phenomenon that describes the behavior of workers who choose to quit doing work that is not their main job at work, and become less psychologically invested in work. The approach in this study uses quantitative research methods. There were 377 research subjects spread across 21 provinces in Indonesia. The results of this study indicate that employee engagement and well being owned by workers are high. This study illustrates that workers are able to psychologically invest both cognitive, emotional and behavioral in the work they do. Even workers feel psychologically prosperous in carrying out work. Based on these results, it appears that the workers in this study show committed behavior in carrying out their jobs.Keywords: Engagement, Quiet Quiting, Well Being, Worker